2016
DOI: 10.1007/s10548-016-0505-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Infant Covert Orienting, Sustained Attention and Brain Activity

Abstract: This study used measures of event-related potentials (ERPs) and cortical source analysis to examine the effect of covert orienting and sustained attention on 3- and 4.5-month-old infants’ brain activity in a spatial cueing paradigm. Cortical source analysis was conducted with current density reconstruction (CDR) using realistic head models created from age-appropriate infant MRIs. The validity effect was found in the P1 ERP component that was greater for valid than neutral trials in the electrodes contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 80 publications
1
47
1
Order By: Relevance
“…This explanation is in line with previous research that has reported the effects of sustained attention on infants’ visual processing of target stimuli (Hunter & Richards, 2003; Mallin & Richards, 2012; Richards, 2004; Xie & Richards, 2016). In these studies, infants’ reaction time and their ERP responses to the visual targets were improved during sustained attention.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This explanation is in line with previous research that has reported the effects of sustained attention on infants’ visual processing of target stimuli (Hunter & Richards, 2003; Mallin & Richards, 2012; Richards, 2004; Xie & Richards, 2016). In these studies, infants’ reaction time and their ERP responses to the visual targets were improved during sustained attention.…”
Section: Discussionsupporting
confidence: 92%
“…It can be seen in Figure 6 that the N290 is evident in both lateral and medial posterior regions. However, the N290 response in the three medial posterior channels (Occipital-Inion1, Occipital-InionZ, Occipital-Inion2) was affected by or mixed with the N1 component that was most prominent in these regions (Richards, 2005; Xie & Richards, 2016). In contrast, the N290 component in the four lateral electrode clusters (Parietal9, Parietal10, Parietal-Occipital7–9, Parietal-Occipital8–10) was not influenced by the N1 component and appeared to have clearer peaks (cf.…”
Section: Resultsmentioning
confidence: 91%
“…The steps of source analysis are selection of anatomical MRI, construction of realistic head models, distributed source reconstruction, and segmenting source activity in the whole brain into ROIs. Details about each step are described in the Supplemental Information and in Xie and Richards (2016b).…”
Section: Methodsmentioning
confidence: 99%
“…Infant sustained attention has been found to enhance infant ERPs components subserving different brain functional networks (Guy, Zieber, & Richards, 2016; Reynolds & Richards, 2005; Xie & Richards, 2016a, b). The changes in these ERP components provide evidence for the consequences of infant sustained attention effects on brain activity.…”
Section: Measurements and Functions Of Infant Sustained Attentionmentioning
confidence: 99%
See 1 more Smart Citation